Daydreaming Dynasty: The Eunuch Sanbao's Journeys in the Western Seas and "Present-Dynasty" Fiction of the Ming. (March 2015) - Gregory, Scott W.
Abstract : Though many novels produced in the Ming dynasty were based on historical subjects, only a very few were inspired by historical events of the Ming itself. Of those few that were, the so-called "present-dynasty novels, " by far the most complex was the Sanbao taijian xiyang ji 三寶太監西洋記, or The Record of the Eunuch Sanbao's Journeys in the Western Seas . Published in 1598, the novel is a highly fictionalized account of the voyages of Zheng He, which had occurred nearly two centuries previous. Due to the fantastical elements of its plot, the Sanbao is often regarded as a mere adventure story. This paper argues that, to the contrary, the novel skillfully blends history and fiction to reflect concerns of the late Ming era. The paper demonstrates how the novel makes self-conscious reference to other well-known works of fiction, highlighting its own fictionality at the same time it depicts "historical" figures and events. It also argues that the novel's use of the lost imperial seal of state as the journey's impetus reflects anxieties about the legitimacy of the dynasty and also cleverly solves the problem of "present-dynasty" fiction.